Structural and microtectonic analyses of Barpak of Gorkha district, west-central Nepal (Journal of Nepal Geological Society, 2020)
Geological mapping was carried out in the Barpak-Bhachchek area of the Daraudi River valley, Gorkha district, West-Central Nepal for structural analysis. The area comprises rocks of the Higher Himalayan Crystalline and the Lesser Himalayan Sequence.  Pelitic and psammitic schist, quartzite, calc-quartzite, dolomitic marble, graphitic schist, gneiss are the main rock types within the Lesser Himalayan Sequence,  whereas banded gneiss and quartzite form a significant portion of the Higher Himalayan Crystalline in the study area. The area is affected by poly-phase deformation. Lesser Himalayan Sequence has suffered five deformational phases (DL1-DL2, D3-D5) whereas the Higher Himalayan Crystalline has suffered four deformational events (DH1, D3-D5). The Lesser Himalayan Sequence lying to the northern limb of the Gorkha-Kuncha Anticlinorium is contort into doubly plunging to dome-and-basin-like en echelon type of non-cylindrical folds as Baluwa Dome and Pokharatar Basin (DL2 and D4). The direction of shearing as indicated by shear sense indicators (C' Shear band and Mica fish) is top-to-south coinciding with regional sense of shear related to the MCT propagation. The dynamic recrystallization direction, obtained from rock dominant with phyllosilicate minerals is top-to-south and coincides with mineral lineation and indicate the mineral lineation is contemporary with dynamic recrystallization during the MCT propagation.